Effects of porosity on free vibration and nonlinear dynamic response of multi-layered functionally graded materials subjected to blast loads - Đỗ, Thị Thu Hà (2020)
The effects of porosity ratio on free vibration andnonlinear dynamic response of FGM sandwich plates with twoFGM face-sheets and a homogeneous core as ceramic resting on elastic foundationssubjected to blast load are investigated in this thesis by implementing the third-order shear deformation theory. Two types of porosity are proposed, namely evenly distributed porosity and unevenly distributed porosity. Assumption that the material properties of multi-layered FGM plate to be changed in the thickness direction accord with a simple-power law distribution with regard to the volume proportion of thecomponents. This study obtainsnumerical results by using the Galerkin method and fourth-order Runge-Kutta method illustrating the significant effects of porous fractions, geometrical parameters, the elastic foundation, blast loads on the nonlinear dynamic response of FGM sandwic h plates